2020
DOI: 10.4103/ijo.ijo_1492_19
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study to assess the role of vitamin D individually and in combination with cyclosporine in the treatment of dry eye in patients with deficient serum 25(OH)D levels

Abstract: Purpose: To study the efficiency of vitamin D3 (buccal spray) alone and combination of vitamin D3 with cyclosporine in the treatment of dry eye disease (DED) in patients with deficient serum 25(OH)D levels. Methods: Around 90 patients with DED with deficient serum 25(OH)D levels were included and randomized into three groups and were given treatment for dry eye (Group A- 0.5% carboxymethylcellulose (CMC), Group B- 0.5% CMC + 2000 IU vitamin D through buccal spray, Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
0
20
0
4
Order By: Relevance
“…These are in agreement with findings, of Bae et al (11) which concluded that the mean age of the patients was 58.21 ± 12.94 years and included 21 men and 84 women. In another prospective-randomized study of Watts et al (12) in which 90 patients with DED with deficient serum 25(OH) D levels were randomized into three groups and were given treatment for dry eye. Out of 90 patients, 52 were females and 38 were males with a mean age of 44.87 ± 14.77 (range = 20-80) years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are in agreement with findings, of Bae et al (11) which concluded that the mean age of the patients was 58.21 ± 12.94 years and included 21 men and 84 women. In another prospective-randomized study of Watts et al (12) in which 90 patients with DED with deficient serum 25(OH) D levels were randomized into three groups and were given treatment for dry eye. Out of 90 patients, 52 were females and 38 were males with a mean age of 44.87 ± 14.77 (range = 20-80) years.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many etiological factors, an association of Vitamin D deficiency with DES and tear film insufficiency has received attention in recent studies. The prevalence of vitamin D deficiency in India has been reported to be 80%-90% in most studies (13) , a study of Watts et al (12) and Aparna et al (14) defined the deficiency as a serum vitamin D level of < 20 ng/ml. However, another study of Yoon et al (15) has taken < 12 ng/ml as the cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…An improvement in cornea epithelial bore has been reported in patients with vitamin D supplementation, because it regulates narrow joints between cells 10 . In addition, vitamin D immunomodulatory mechanisms have been proposed in in ammatory eye processes, expressed in inhibition of in ammatory cell migration (Th1 and Th2 cells), increased interleucine synthesis (IL) 10, reduction of in ammatory cytokines such as IL6, C-reactive protein and tumor necrosis factor (TNF) alpha 11,12 . Other described functions of this vitamin is act as a stabilizer of the eye surface, through the reduction of the osmolarity of tears 12 .…”
Section: Introductionmentioning
confidence: 99%
“…published in this issue of the Indian Journal of Ophthalmology. [ 1 2 3 4 ] The prevalence of vitamin D deficiency in India has been reported to be 40%–99% (80%–90% in most studies). [ 5 ] Most studies define the deficiency as a serum vitamin D level of <20 ng/ml;[ 4 5 ] however, some studies[ 2 ] have taken <12 ng/ml as the cutoff.…”
mentioning
confidence: 99%
“…[ 6 ] Vitamin D induces the production of IL10 and reduces inflammatory cytokines/factors like IL1, IL6, TNF alpha, and C-reactive protein. [ 4 ] In addition, vitamin D reduces inflammation by increasing antioxidant cytokines in tears and suppressing both Th1 and Th2 cells. [ 7 ] Vitamin D induces D cathelicidin, which promotes the wound healing of conjunctiva and cornea.…”
mentioning
confidence: 99%